2018
DOI: 10.1002/hep.29616
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte DUSP14 maintains metabolic homeostasis and suppresses inflammation in the liver

Abstract: Hepatocyte DUSP14 is required for maintaining hepatic metabolic homeostasis and for suppressing inflammation, a novel function that relies on constraining TAK1 hyperactivation. (Hepatology 2018;67:1320-1338).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…In the current study, our results showed that HFD feeding resulted in significantly enhanced TAK1 phosphorylation, JNK1 phosphorylation and IRS1 phosphorylation and reduced Akt phosphorylation in liver of rats, which was consistent with previous research (An et al, ; Ji et al, ; P.X. Wang et al, ; S. Wang et al, ; Yan et al, ; Zhao et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, our results showed that HFD feeding resulted in significantly enhanced TAK1 phosphorylation, JNK1 phosphorylation and IRS1 phosphorylation and reduced Akt phosphorylation in liver of rats, which was consistent with previous research (An et al, ; Ji et al, ; P.X. Wang et al, ; S. Wang et al, ; Yan et al, ; Zhao et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Further research provided mechanistic evidence that hepatic dual‐specificity phosphatases 14 (DUSP14), directly binds to and dephosphorylates TAK1, resulting in reduced TAK1 phosphorylation and its downstream signaling molecules JNK1, thereby improves insulin sensitivity (S. Wang et al, ). Other research revealed that hepatic ubiquitin specific protease 4 (USP4) and ubiquitin specific protease 18 (USP18), which is also known as UBP43 (L.Q.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that an appropriate level of TAK1 is essential for maintaining physiological functions in the liver. By contrast, consistent with our findings, other studies indicated that hyperactivation of TAK1 promoted HFD‐induced hepatosteatosis and TAK1 suppression was protective against the pathogenesis of NAFLD . Congruently, the same phenomenon was reported in the cardiovascular system.…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that DUSP14 expression decreases during diverse inflammatory states (Jianrong et al, 2019;Zhang et al, 2019;Xia et al, 2019), which is thought to promote inflammation and pathology. DUSP14-deficient mice have enhanced susceptibility to experimental autoimmune encephalitis (Yang et al, 2014), aortic banding-induced cardiac hypertrophy and dysfunction (Li et al, 2016), hepatic and cardiac ischemia-reperfusion injury (Wang et al, 2017b;Lin et al, 2018), and high-fat diet-induced hepatic dysfunction (Wang et al, 2018), all of which have been attributed to its role in MAPK regulation. As necroptosis has been shown to be pathogenic in the aforementioned diseases (Galluzzi et al, 2017), it will be of interest to investigate whether the phenotype of Dusp14 À/À mice in disease models can be attributed to excessive necroptosis.…”
Section: Discussionmentioning
confidence: 99%